Evaluation of vancomycin pharmacokinetics in patients with augmented renal clearances: A randomized clinical trial - Sahraei, Zahra; Saffaei, Ali; Alavi Darazam, Ilad; Salamzadeh, Jamshid; Shabani, Minoosh; Shokouhi, Shervin; Sarvmeili, Najmeh; Hajiesmaeili, Mohammadreza; Zangi, Masood (Frontiers in Pharmacology, 2022)
Purpose: Vancomycin is a narrow therapeutic window glycopeptide antibiotic that acts against Gram-positive bacteria. As it is renally eliminated, therapeutic drug monitoring is recommended for vancomycin, especially in case of kidney function alteration. Augmented renal clearance (ARC), defined as a creatinine clearance of more than 130 mL/min, is a risk factor for sub-therapeutic concentrations of vancomycin. This study aimed to evaluate the vancomycin pharmacokinetics following the administration of two different regimens in ARC patients. Methods: A randomized clinical trial (IRCT20180802040665N1) was conducted on patients in need of vancomycin therapy. Eight hours of urine was collected and 56 patients divided into two groups with creatinine clearance of more than 130 mL/min were included in the study. The first group received 15 mg/kg of vancomycin every 12 h and the second group 15 mg/kg every 8 h. After four doses, the peak and trough concentrations were measured from two blood samples. The primary outcome was the percentage of patients who attainted AUC more than 400. The occurrence of acute kidney injury also was evaluated after seven days. Results: The mean age of patients in the every 12 h and every 8 h groups was 44.04±16.55 and 42.86±11.83 years, respectively. While neurosurgical issues were the most common causes of hospitalization, central nervous infections were the most common indications for vancomycin initiation. Urinary creatinine clearance was 166.94±41.32 mL/min in the every 12 h group and 171.78±48.56 mL/min in the every 8 h group. 46.42% of patients in the every 12 h group and 82.14% of patients in the every 8 h group attained AUC/MIC of more than 400 mg×hr/L. None of the patients in the every 12 h group reached more than 15 mcg/mL concentration. At the 7-day follow-up, 10.7% patients in the BD group and 28.6% patients in the TDS group developed acute kidney injury (P= 0.089). Conclusion: Administration of vancomycin at a dose of 15 mg/kg every 8 hours is associated with higher pharmacokinetic attainment in ARC patients. The occurrence of acute kidney injury also was not significantly higher in this therapeutic regimen. AUC/MIC monitoring is necessary in this population.